Karakteristik Campuran AC-BC Menggunakan Slag Nikel PT. Vale Sebagai Pengganti Agregat - Kevin Matasik Rante Padang (Paulus Civil Engineering Journal, 2025)
The use of green materials for road work construction is urgently needed in order to create sustainable construction. One of the green materials that can be used is nickel slag found in PT. Vale Sorowako. This research is intended for the utilization of nickel slag of PT. Vale Sorowako in AC-BC mixture and to obtain the characteristic value of filler, fine and coarse aggregate and then the composition of the AC-BC mixture is carried out, as well as to obtain the characteristics of the mixture is carried out by marshall test and to obtain the results of the stability of the residual marshall. The guideline used in this study is SNI 03-1737-1989. The use of 100% aggregate of nickel slag and asphalt content of 5.00%-7.00% with an interval of 0.5% results in an optimum of 7.00% and meets for all test results for marshall characteristics. And for the results of KAO at asphalt content of 7.00% through marshall immersion testing on AC-BC mixture, Marshall stability was obtained Residual by 104.91%